Anesthesia for bilateral pulmonary banding as part of hybrid stage I approach palliating neonates with hypoplastic left heart syndrome. Issue 6 (30th April 2020) - Zajonz, Thomas; Cupka, Pavol; Koerner, Christian; Mann, Valesco; Menges, Thilo; Akintuerk, Hakan; Valeske, Klaus; Thul, Josef; Schranz, Dietmar; Mueller, Matthias
Abstract: Background: Neonatal management of patients with hypoplastic left heart syndrome and complex remains a challenging task, whereby the "hybrid" palliation is often reserved for high‐risk patients as a "rescue" procedure. Aim: This study documents the anesthetic challenges and potential complications associated with the Giessen hybrid stage I approach. Methods: The Giessen hybrid stage I approach is focused on surgical bilateral pulmonary artery banding. Retrospective perioperative data were analyzed. Contrary to a stable group A, inotropic treatment before surgery for treatment of postnatal shock classified patients as unstable (Group B). Clinical outcomes considered were inhospital mortality, duration of postoperative mechanical ventilation, postoperative time at the intensive care unit, perioperative vasoactive medication requirements, and red blood cell transfusion. Results: From June 1998 to December 2015, 185 patients were allocated to Group A (n = 165) and Group B (n = 20). The inhospital mortality was 2.2% with no difference between the groups. There was also no difference in the postoperative time on mechanical ventilation and the time in the intensive care unit. Vasoactive medication was more often required in Group B (100%) compared to Group A (19%). In Group B, more red blood cells were transfused 6.0 ± 8.3 vs 2.0 ± 5.8 mL/kg in Group A ( P < .05, 95% CI 0.0 ‐ 2.6). Conclusion: Considering a learning curve, anesthesia for surgical bilateral pulmonary artery banding palliating patients with hypoplastic left heart syndrome and complex can safely be performed, independent from the preoperative clinical status.